Euthanasia in Dementia: A Narrative Review of Legislation and Practices in the Netherlands and Belgium - Marijnissen, Radboud M.; Chambaere, Kenneth; Oude Voshaar, Richard C. (Frontiers in Psychiatry, 2022)
Euthanasia was first legalised in the Netherlands and Belgium in 2001 and 2002 respectively. Currently they are among the few countries that also allow euthanasia on the basis of dementia, which is still considered controversial, both from a scientific and societal perspective. To date, euthanasia in dementia constitutes a small proportion of all Dutch and Belgian euthanasia cases. However, instances are rising due to a growing awareness among the general public about the possibilities of a self-chosen end-of-life and the willingness among medical professionals to perform euthanasia in individuals diagnosed with dementia. In both countries euthanasia is allowed under strict conditions in patients with dementia and decisional capacity regarding euthanasia, while in the Netherlands an advance euthanasia directive can also replace an oral request for euthanasia in those with late-stage dementia. Judging euthanasia requests from patients with dementia is complex and the assessment of the due care criteria (especially those related to decisional capacity and unbearable suffering) requires caution and great care. In this narrative review, we reflect on the legal regulation, clinical guidelines and societal debate regarding euthanasia in dementia in the Netherlands and Belgium. By discussing the 20 years of experience with the ethical dilemmas and controversial aspects surrounding this delicate topic, we hope to inform the preparation or implementation of new legislation on euthanasia in dementia in other countries.